Non-Terrestrial Network Based Positioning Technologies for Direct-to-Satellite Service - SUN Xiaonan; ZHOU Shidong; KANG Shaoli (天地一体化信息网络)
With the rapid evolution of wireless communication technologies, positioning technologies are undergoing a transformation from dedicated navigation satellite systems towards communication system-assisted positioning and even standalone positioning. The International Telecommunication Union's 3GPP, since Release 18, has embarked on researching 5G Non-Terrestrial Network (NTN) positioning technologies, fostering the integration of communication and navigation. Considering the limited visibility of satellites to terminals, the primary focus of current 3GPP research lies in single-satellite positioning technology, which suffers from drawbacks such as slow convergence and low accuracy. However, with the emergence of low-Earth orbit mega-constellations, terminals will access to an increasing number of visible satellites in the future, rendering multi-satellite positioning feasible. Compared to single-satellite positioning, multi-satellite positioning offers advantages such as faster convergence, improved geometric configurations and higher accuracy.This paper delves into the research of positioning technologies for Direct-to-Satellite Service (D2SS) within the 5G NTN framework, proposing various multi-satellite positioning algorithms, analyzing the critical factors influencing positioning performance, and conducting simulation assessments of positioning performance.